Profit Quality, Islamic Corporate Social Responsibility And Company Values: Islamic Corporate Governance As Moderation - Maharani, Elda; Kurniawan, Heri (JPS (Jurnal Perbankan Syariah), 2024)
This study aims to analyze the effect of profit quality and Islamic corporate social responsibility (ICSR) on firm value moderated by Islamic corporate governance (ICG). This study uses a quantitative approach. The population used is all Islamic Commercial Banks (ICB) registered with the Financial Services Authority (FSA) in 2018-2023. The sampling technique used purposive sampling and obtained 11 ICB samples. The data source used is secondary data in the form of documentation of each BUS's financial statements. This study uses multiple linear regression analysis techniques. The results of this study indicate that profit quality negatively affects firm value. ICSR positively affects firm value. ICG is unable to moderate the relationship between profit quality and firm value. ICG is unable to moderate the relationship between ICSR and firm value. This study can complement existing theories and be a reference for future research. This study can also be a reference for ICB in increasing ICB value, especially regarding profit quality and ICSR.